L’Éducation sentimentale : genèse de la rencontre entre Frédéric et Mme Arnoux - Éric Le Calvez (Flaubert: Revue Critique et Génétique)
The first encounter between Mme Arnoux and Frédéric Moreau, main characters of L’Éducation sentimentale, appears very early in its genesis as it is visible from the first scenarios. It is inevitable, of course, in the case of what will become a love story. It is associated to the theme of water and then of travel, as the scene is not a static one, and undergoes numerous variations in the manuscripts, which is obvious with Flaubert. However, it can be concluded that he did not suffer for a long time to write it, because he found its general movement rather fast.